Rapid Detection of Respiratory Pathogens for Community-Acquired Pneumonia by Capillary Electrophoresis-Based Multiplex PCR. (February 2019) - Li, Xue; Chen, Bo; Zhang, Shaoya; Li, Xiuyuan; Chang, Junxia; Tang, Yanyan; Wu, Yong; Lu, Xinxin
Community-acquired pneumonia (CAP) is a common infectious disease linked to high rates of morbidity and mortality. Fast and accurate identification of the pathogens responsible for CAP will aid in diagnosis. We established a capillary electrophoresis-based multiplex PCR (CEMP) panel to enable the detection of viral and bacterial pathogens associated with CAP. The assay simultaneously detects and identifies the 13 common unculturable CAP viral and bacterial pathogens within 4 h. We evaluated the performance of a commercially available panel with 314 samples collected from CAP patients. We compared the results to those obtained with the liquid chip-based Luminex xTAG Respiratory Viral Panel (RVP) Fast Kit (for viruses) and the agarose gel-based Seegene PneumoBacter ACE Detection Kit (for atypical bacteria). All positive samples were further verified by the Sanger sequencing method. The sensitivity, specificity, positive predictive value, and negative predictive value of CEMP were 97.31%, 100%, 100%, and 99.85%, respectively. CEMP provides a rapid and accurate method for the high-throughput detection of pathogens in patients with CAP.